Lambda production in 40 A GeV/c Pb-Au collisions - Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Drees, Axel; Esumi, ShinIchi; Filimonov, Kirill; Glässel, Peter; Milošević, Jovan; Petráček, Vojtech; Schmitz, Wolfgang; et al. (Arxiv, 2002)
During the 1999 lead run, CERES has measured hadron and electron-pair production at 40 A GeV/c beam momentum with the spectrometer upgraded by the addition of a radial TPC. Here the analysis of lambda and antilambda will be presented.
Gesehen am 28.02.2018